Socializing relations in the everyday lives of children: Comparing domestic texts from Norway and China. (February 2013) - Wærdahl, Randi; Haldar, Marit
The text material analysed in this article consists of 20 teddy-diaries that circulated between the families of 6-year-old children in Beijing, China and in Oslo, Norway. The circulation process makes teddy-diaries highly normatively saturated domestic stories from families with 6-year-old children. A quantitative analysis of these texts inspired by Membership Categorization Analysis (MCA) developed by Harvey Sacks (1972) reveals what is deemed significant relations for children in each culture. By identifying actions and contexts that are described as relevant and appropriate for these significant relations, the researcher can also achieve a better understanding of how these relations are constructed as socializing relations in the everyday lives of children. The article finds that the learning styles and positioning of the child in everyday lives is participatory, play and peer oriented in Norway and instructional, encouraging and progress oriented in China.